THE DESCRIPTION OF ACADEMIC BOREDOM AMONG FEMALE STUDENTS AT PONDOK PESANTREN PUTRI X - Lailatul Lutfiya; Ghozali Rusyid Affandi; Wiwik Triwidiyanti (Universitas Muhammadiyah Surabaya, 2025)
Islamic boarding schools are areas that have their own sub-cultures which are broadly divided into three types, namely salafiyah (traditional), khalafiyah (modern), and intergrated. This study was conducted on students of islamic boarding school X which is a salafiyah (traditional) islamic boarding school. This study aims to determine the existence of academic boredom triggered by daily activities with a busy, monotonous schudele, and same environment that triggers feeling of boredom and fatigue. This study used 206 samples from 206 students of class 3 Mts. The sampling technique used saturated sampling with the measuring intrument The Achievement Emotions Questionnaire (AEQ). Data analysis used in this study is descriptive using microsoft excel. Based to the overall data that has been obtained, students of class 3 Mts at the X female islamic boarding school experiebced academic boredom in the moderate catagory with a value of 63%, the low category 19 and the high category 18%.